“Who comes next?”: Planning and managing sustainable initiatives that facilitate family business succession - Prazeres, V. M. C. E.; Ferreira, F. A. F.; Ferreira, N. C. M. Q. F.; Ferreira, J. J. M.; Meidute-Kavaliauskiene, I. (Journal of Family and Economic Issues)
Family businesses are increasingly recognized for their significance in the global economy, constituting a growing portion of companies worldwide and elevating the importance of this topic on governmental agendas. Unique challenges confront family firms, intertwining business decisions with familial repercussions. Among these challenges, the succession process emerges as a critical threat to their continuity. Inadequate solutions to the question of succession often lead to organizational failure, underscoring the urgency of addressing this issue. This study endeavors to construct an analysis model to support decision-makers throughout the succession journey, integrating a constructivist approach that merges cognitive mapping and interpretive structural modeling (ISM). This dual methodology facilitates the swift identification and analysis of factors crucial for smoother family business succession. The model development leverages insights from an expert panel and entails delineating cause-and-effect relationships among identified determinants and prioritizing these factors based on their significance. Subsequently, the model undergoes validation through a consolidation session with experts from the Associação de Empresas Familiares (i.e., Family Business Association in Portuguese), who assess its practical applicability. This includes perspectives from a Brazilian expert renowned for his understanding of family business dynamics within an emerging economy—Brazil. The insights gleaned from these sessions inform recommendations on implementing the tested procedures within real-life family enterprises, thereby contributing to the sustainability and longevity of these businesses.